CO2 capture with the help of Phosphonium-based deep eutectic solvents - Ghaedi, H. (Elsevier B.V., 2017)
Deep eutectic solvents (DESs) are derived from the concomitant reaction of two or more salts i.e. between hydrogen bond acceptor (HBA) and hydrogen bond donors (HBD) components. In this work, DESs were prepared namely allyltriphenyl phosphonium bromide-diethylene glycol (ATPPB-DEG) and allyltriphenyl phosphonium bromide-triethylene glycol (ATPPB-TEG) into three molar ratios 1:4, 1:10, and 1:16 salt to HBDs. The carbon dioxide solubility in DESs at temperature of 303.15 K and pressure up to 2 MPa were determined and reported in terms of mole fraction, CO2 loading and Henry's law constants. Krichevsky–Kasarnovsky equation was used to correlate the solubility data and obtain Henry's law constants at 303.15 K. Finally, the effects of hydrogen bonding within DESs, molar ratio, molar volume, free volume, ether group and alkyl chain length were investigated based on CO2 solubility in DESs. To the best of our knowledge, this is the first time CO2 solubility in these DESs was studied. © 2017 Elsevier B.V.